In vitro biosynthesis of beta-endorphin in pituitary glands. - Crine, P (1977)
beta-Endorphin is a 31 amino acid polypeptide isolated from the pituitary gland of different species of animals. It has strong morphine-like activity. It is formed of amino acid residues 61-91 of beta-lipotropin. Speculation has arisen whether it is biosynthesized in situ or transformed after secretion of beta-lipotropin. The present in vitro studies show that it is found as beta-endorphin in bovine pituitary slices incubated with radioactive amino acid precursor [35S]methionine. Chemical characterization and microsequencing of the newly biosynthesized material proves its identity with isolated unlabeled beta-endorphin and shows that it has a methionine residue at its fifth position, as expected.